Non-genetic factors in pre-weaning growth performance of wool biotype lambs in the Colombian highland tropics - Cuello Estrada, María Alejandra (2019)
The objective of this study was to evaluate the effect of non-genetic factors on the characteristics of pre-weaning growth in sheep under tropical conditions. The sex of the lamb, the type of birth (single, multiple) and parity number on the birth weight, weaning weight and preweaning daily gain of 52 wool biotype lambs were evaluated. The lambs were weighed weekly from birth to week 12 (weaning). The sex of lambs did not have a significant effect on the variables evaluated. Lambs from mothers of third lambing had a higher preweaning daily gain than lambs from mothers of first lambing (p<0.05). Singleborn were heavier at birth and at weaning than lambs born as twins (p<0.05). It is concluded that the type of birth is the factor that mainly affects the characteristics of preweaning growth and that the sex of the offspring and lambing number do not significantly affect the growth performance.